Changes of Malay Reserve Land (MRL) area under status of pelan warta in Johor - Noormasmalyanah Masli, 1992- author (Johor Bharu : Universiti Teknologi Malaysia, 2016)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik)), Universiti Teknologi Malaysia, 2016